Determination of Fluoride Levels of Sakarya City Drinking Water by Ion-Selective Electrodes and Ion Chromatography - Hüseyin Altundağ; Çiğdem Yüceel; Mustafa Şahin Dündar; Sinem Albayrak (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2011)

(untitled)
Fluoride, next to industrial use of the biological importance of a element. Therefore the levels of floride in the drinking water are important because of public health. In this study, a total 10 samples are taken from 9 different points, which contain drinking water in Sakarya, center and regions of the city (Kampüs, Serdivan, Ozanlar, Camili, Karaman, Erenler1, Erenler2, Cark Caddesi, Hızırtepe and Dortyol). In these samples, determination of flouride was made with ion selective electrode and ion chromatography methods. World Health Organisation (WHO) suggests flouride amount in drinking water less than 1,5 mg/L. In drinking water samples which are taken from Sakarya, center and regions of the city avarage flouride values were determined in accordance with standards less than 1,5 mg/L.